Improving the Financial Management of Local Economic Enterprises - Rosario G. Manasan; Cynthia G. Castel (Philippine Institute for Development Studies (PIDS), 2010)
Although LEEs are meant to be self-sustaining, if not revenue-generating units, many of them actually incur losses on a continuing basis. Current practice in many LGUs does not engender a clear appreciation of the true cost of the local economic enterprise. COA has documented many cases where the operation of LGU economic enterprises was not treated as special accounts in the General Fund contrary to the provisions of the Local Government Code (LGC) of 1991. The less than transparent reporting of the actual financial condition and profitability of these enterprises may have some adverse effect on decisions taken by LGU officials. On the one hand, economic enterprises are oftentimes used as the vehicle for charging casual employees who are utilized elsewhere in the LGU system so as to circumvent the 45 percent-55 percent limitations on personal services (PS) expenditures of LGUs. On the other hand, part of the cost of LEE operation and management is sometimes charged under other offices in the LGU. Overall, the less than business-like approach to local enterprise management has resulted in large arrearages and low collection efficiency.
Keywords: 330; public enterprise; economic enterprise; state-owned enterprise; alternative service delivery modes; government budgeting; one-fund principle; cost recovery; Standortpolitik; Öffentliches Unternehmen; Privatwirtschaft; Kosten-Nutzen-Analyse